A return to innocence: Guimi tourism and women empowerment. (20th April 2021) - Hao, Fei; Zhang, Shiqin; Xiao, Honggen
Abstract: Influenced by the Confucian culture, clan‐family structure, and communist ideology, gender inequality still widely exists in modern China. On reflection of the socio‐cultural framework that shaped the Chinese gender lens, this study took a "power to" perspective on women empowerment by investigating 28 Guimi‐tourists ' embodied experience. Upon identifying the core experience of "Return to Innocence, " a resources‐agency‐achievements framework was constructed to depict the underlying mechanism through which Guimi tourism empowered women to counteract sociocultural constraints. The study offered a context‐specific understanding of Guimi tourism and theoretically contributed to women empowerment and tourism, as well as Chinese cultural studies.